If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 10 = -23 Reorder the terms: 10 + 3x = -23 Solving 10 + 3x = -23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 3x = -23 + -10 Combine like terms: 10 + -10 = 0 0 + 3x = -23 + -10 3x = -23 + -10 Combine like terms: -23 + -10 = -33 3x = -33 Divide each side by '3'. x = -11 Simplifying x = -11
| 4x(x^2-2x)=0 | | (4x+11)+(6x-1)=180 | | x^2+2x=390 | | 7x+1x=12x+24+8x | | .6x+6=.5x+.75x | | -6+7x=36 | | -4r=24 | | .75x+6=.5x+.25x | | 4x+2(x-50)=172 | | 7x+1x=4x+24+8x | | 4x+2(50-x)=172 | | 5(0.6x-7)=-35 | | u^2-4=0 | | 2x+4(50+x)=172 | | x+(x-7.5)=2(x-7.5) | | -2(-3x+3)=0 | | (X-8)(x-23)=0 | | u^2-2y=0 | | 8x+1x=12x+40+5x | | 4(3x+9)=144 | | 4x+2(50+x)=172 | | 4x+2(50+x)= | | 4(6x+4)=16 | | -6(9-7x)=156 | | Ln(x+3)=-1 | | 8+2x=-2 | | 6x-0.88=29.1 | | 6x-10=-12 | | 7.4=55m | | 190+4x+x=540 | | 10x^2+5x-16=0 | | -5x+3=0.2 |